Influence of Soil Nutrients, Tree Age, and Sandalwood Provenances on Sandalwood Oil Yield and Quality - Mary Gathara; Bernard Kamondo; Riziki Mwadalu; Stephen Omondi; Mercy Kivuti; Norman Wairagu; Tom Oduor; Peter Gachie (International Journal of Forestry Research)
East African Sandalwood (Osyris laceolata) is an important tree species used in perfumery and pharmaceutical industries. In Kenya, the tree is illegally poached and smuggled mostly to India as a substitute for Asian sandalwood. Therefore, there is a need to domesticate E. A. sandalwood to ease pressure on natural stands. The aim of this study is to determine ecological factors influencing Osyris oil yield and quality to guide the selection of provenances for on-farm domestication. Soil and woody samples were obtained from 12 provenances and used for soil and oil analysis, respectively. The results showed that only tree age significantly influenced the oil yield (r = 0.31, p=0.04). The GC-MS quality results recorded nine common and most abundant compounds across the study sites. These were Z-alpha-trans-bergamotol, alpha bisabolol, lanceol cis, beta bisabolene, alpha santalol, beta santalol, cis-alpha-copaene-8-ol, isopropyl myristate, and isopropyl palmitate. Baringo and Mbooni provenances had the highest number of compounds (8), followed by Homabay (7) while the majority (Chyulu, Kitui, Loita, Maralal, Marsabit, Muranga, and Narosura) had six and Ol Donyo Sabuk and Namanga had the least (5). The species diversity is therefore important for breeding, domestication, and conservation purposes.